Islamic Religious Education Learning Based on Religious Moderation at Senior High School NU Al-Ma’ruf Kudus - Maulana Achmad Hasan Maulana; Agus Salim; Rizaldy Alpiansyah; Irfan Alkhotiri; Dzulfikri (Sekolah Tinggi Agama Islam Minhajul Haq, 2026)
The focus of this research is the learning of Islamic religious education based on religious moderation at Senior High School NU Al-Ma'ruf Kudus. The purpose of this research is to find out: (1) the learning of Islamic religious education based on religious moderation using the insertion method. (2) the supporting and inhibiting factors of learning Islamic religious education based on religious moderation using the insertion method. This research is a qualitative research, using field research. The subjects of this research are the principal, curriculum vice principal, Islamic religious education teacher, and students. The results of this research are: (1) the implementation of learning Islamic religious education based on religious moderation at Senior High School NU Al-Ma'ruf Kudus, namely: a) the planning stage, teachers must prepare the material to be taught to students. b) the implementation stage, Islamic Religious Education teachers teach in class with material according to KD (Basic Competencies) and textbooks then insert the character value of religious moderation according to the 21st Century RPP based on the character value of the Pancasila student profile (PPP) and the value of religious moderation according to Permendikbud No. 37 of 2018 c) learning evaluation stage. (2) Supporting factors for learning Islamic religious education based on religious moderation at Senior High School NU Al-Ma'ruf Kudus are as follows: a) The school organization is a 1 command system. b) Islamic Religious Education teachers are competent and understand the material on religious moderation. c) Adequate facilities, while the inhibiting factors are as follows: a) teachers must make thorough preparations before learning begins. b) socialization of religious moderation has not been maximized in schools from the Ministry of Religion. c) the influence of social media. d) the influence of social interactions outside of school. e) the diversity of students' school origins.